Biarylsulfonamide CCR9 inhibitors for inflammatory bowel disease. Issue 17 (1st September 2015) - Zhang, Jing; Romero, Jan; Chan, Audrey; Goss, Jennifer; Stucka, Sabrina; Cross, Jason; Chamberlain, Brian; Varoglu, Mustafa; Chandonnet, Haoqun; Ryan, Dominic; Lippa, Blaise
Graphical abstract